The Cambridge economic history of the modern world. Volume II, 1870 to the present - Broadberry, S. N.; Fukao, Kyōji (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2021)
The second volume of The Cambridge Economic History of the Modern World explores the development of modern economic growth from 1870 to the present. Leading experts in economic history offer a series of regional studies from around the world, as well as thematic analyses of key factors governing the differential outcomes in different parts of the global economy. Topics covered include human capital, capital and technology, geography and institutions, living standards and inequality, trade and immigration, international finance, and warfare and empire.
Volume I. 1700 to 1870 -- Volume II. 1870 to the present.
Title from publisher's bibliographic system (viewed on 04 Jun 2021).
Keywords: Industrial revolution -- Great Britain -- History; Economic history; Industrial revolution -- History; Great Britain -- Economic conditions -- 1760-1860; Great Britain -- Economic conditions